MENULIS DIARY DAN IMPLIKASINYA TERHADAP LITERASI PENDIDIKAN - Yusriadi, Yusriadi; Asfar, Dedy Ari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to describe the learning to write a diary (diary) and literacy activities among students, as well as the results achieved in that learning. This study is important because literacy is a major part of civilization and future-building efforts. This research is qualitative research with documentation study. The Data is taken from the records of students who have completed the diary writing program. Diary writing Program has been implemented in the lecture hall at Iain Pontianak since a few years ago. Those who take the subject of Indonesian language courses have been required to keep a diary as part of daily tasks. Researchers have taken writings that contain student recognition of the benefits of writing a diary for life. In conclusion, all students admitted that they benefited from the activity of keeping a diary. The benefit is not only about how to write, but also related to life skills. Getting used to writing makes them have material for self-healing and evaluating how to deal with others. They also claim to be more expressive in life than ever before. This study proposes the approach of writing a diary can be a model in learning among students